Pelatihan Membangun Website Portofolio Menggunakan Bootstrap V5.3 Pada Siswa/I SMK Swasta Jambi Medan - Wayahdi, M. Rhifky; Ginting, Subhan Hafiz Nanda; Ruziq, Fahmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Technological developments are happening so fast, one of which is website technology. So that people are required to follow the development of these technologies. However, most of our people still do not understand or understand technology which makes it difficult to achieve the industrial revolution 4.0. In fact, many IT graduates do not have the skills needed by the industry today. Therefore the author carries out community service with the target of SMK students where skills improvement must be carried out as quickly as possible before they enter the world of lectures or the world of work. This activity is training on building a portfolio website using the bootstrap v5.3 framework, which starts from an introduction (basic) to produce the desired website product. The results of this training activity were that the participants were very enthusiastic, motivated, and all succeeded in building a portfolio website as taught with very good results.